PENGKAPASITASAN IBU HAMIL MELALUI PROGRAM “BECOMING MOTHER AND NURTURING WOMEN’S HEALTH” - Ni Kadek Diah Purnamayanti; Ida Ayu Diah Purnamasari; Hesteria Friska Armynia Subratha (Institut Kesehatan Yarsi Mataram, 2026)
Kayuputih Village is a tourist village in Buleleng Regency, located in the highlands overlooking Lovina Beach at the foot of the hill. This geographical contour presents unique issues related to healthcare access, particularly for vulnerable populations such as pregnant women. The goal of this community service activity is to increase the empowerment of all stakeholders to improve the status of mothers and children: families, village midwives, community health center programmers, and the village government. The program is designed to increase the knowledge, skills, and confidence of pregnant women in preparing for motherhood, while simultaneously improving women's overall health and well-being. Through a combination of health education, interactive discussions, and practical demonstrations, participants are empowered to understand maternal health, nutrition, mental readiness, and newborn care. The activity also highlights the importance of maintaining women's physical and emotional health as the foundation for healthy families and communities. Findings indicate that participants gained increased awareness and self-efficacy in managing pregnancy, childbirth, and early childhood care. This increased empowerment is evident in the 80 percent of participants who attended were willing and correctly carried out the stages of breast and newborn care according to the checklist. This initiative contributes to public health promotion by cultivating informed, resilient, and supportive mothers who can effectively nurture future generations.